PENGENDALIAN DIABETES MELITUS MELALUI EDUKASI DAN PEMERIKSAAN KADAR GULA DARAH SEWAKTU DI PERUMAHAN ROTO KENONGO SEWON - Yoki Setyaji; Iin Desminay Duri; Putri Kuniasiwi; Nanik Aryani Putri (Borneo Community Health Service Journal, 2023)
Diabetes Mellitus (DM) is one of many health problems that have an impact on productivity and reduce the quality of human resources. Diabetes is a metabolic disorder characterized by high blood glucose levels and several symptoms including polyuria, polydipsia, polyphagia and weight loss. This community service aims to increase knowledge and awareness in the prevention and management of Diabetes Mellitus and to find out the category of blood sugar levels in the Roto Kenongo Sewon Residential Community, Bantul District, Yogyakarta. The method used is socialization with lectures and discussions as well as checking the current blood sugar (GDS). The number of participants in this community service was attended by 30 participants. The results of this service found that 3 people got GDS results 200 mg/dl in the DM category. The results of education on management of DM, the community was enthusiastic and able to answer several questions during the discussion session.